Identification of Major Diseases of Tomato from Different Locations of Nepal - Manandhar, C.; Baidya, S.; Manandhar, S.; Pant, B.; Sharma, P.; Magar, P.B. (Journal of the Plant Protection Society, 2020)
Abstract available with the full text.